Perbandingan Kadar Hemoglobin dan Indeks Massa Tubuh pada Siswa SMP di Wilayah Urban dan Rural Kabupaten Jember - Efrida Isfihani (Fakultas Kedokteran, 2025)
Body mass index and hemoglobin levels are critical indicators for assessing adolescents' nutritional status and health. Urban and rural areas can affect these hemoglobin levels and body mass index through factors such as physical activity, nutrient intake, air pollution and pesticide exposure. This study aimed to compare hemoglobin levels and body mass index of boy junior high school students in urban and rural areas of Jember Regency. This research is an analytic observational study with a cross-sectional design conducted at SMPN 8 Jember located in urban area of Jember and SMPN 1 Wuluhan located in rura area of Jember. A total of 40 male students with inclusion and exclusion criteria were recruited from each school. They were assesed for hemoglobin level using GCHb finger prick device, while body mass index data are calculated from the measurements of body weight and height. The data was analysed with Independent t-test for hemoglobin level data, and Mann Whitney test for body mass index data. The results showed that the average hemoglobin levels of students in urban areas were higher with p = 0.001 (16.18 ± 1.36 g/dL) compared to rural areas (15.1 ± 1.48 g/dL). Similarly, the average BMI of students in urban areas was higher with p = 0.021 (20.22 ± 4.29 kg/m²) than those in rural areas (17.94 ± 2.56 kg/m²). Therefore, it was concluded that there were statistically significant differences in hemoglobin levels and body mass index between male students in urban and rural areas.
Reupload Repository Mei 2026 :: Finalisasi Repositori File 19 Mei 2026_Kurnadi
Keywords: adolescence; anemia; nutritional status